Numerical analysis of buried mine explosions with emphasis on effect of soil properties on loading - Fiserova, D. (Cranfield University, 2006)
During armed conflicts or peace-support operations, most casualties are attributed to vehicle-landmine accidents and thus, mine protection fea-tures are a prerequisite for vehicles serving in these areas. Previously, mine protection research was predominantly experiment driven and focussed on structural deformation. Soil parameters were not observed and the influence of soil was not considered. Accurate soil modelling is necessary because experimental studies have shown that soil, in particular saturated soil, has a significant effect on the magni-tude of landmine blast loading on a vehicle. This research describes a numerical modelling approach for studying soil-blast interaction in landmine explosions. The numerical analysis is carried out using the non-linear dynamic analysis software, AUTODYN. The research progressed from (1) the explosion of hemispherical charge laid on a rigid surface, through (2) the study of the explosion of mine deployed in dry sand, to (3) the validation of the mine explosion in cohesive soil for different setups. A framework for deriving the model for soil with varying moisture contents was proposed. The subject of the study is prairie soil (cohesive soil). Standard soil laboratory data are used to determine soil properties that are then used to define a numerical soil model. Validity of the modelling procedure was ascertained by comparison with experimental results from the horizontal pendulum series that were conducted at Defence R&D Canada – Suffield. The applicability of the model was ascertained for (i) different soil types, (ii) varying moisture content, (iii) different mine deployment, and (iv) various high explosive. The numerical results are in reasonable agreement for all observed range of the moisture content. The model and the methodology is generic and extensible and it is argued that such models greatly complement mine experiments.